Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 1-10 - Cumulative Review - Page 696: 9



Work Step by Step

Solving the system of equations using substitution, we find: $$ 5\cdot \frac{1+\frac{-z-7}{5}-z}{2}-\frac{-z-7}{5}+3z=0 \\ z=-2 \\ y=\frac{-\left(-2\right)-7}{5}=-1 \\ x=\frac{1-1-\left(-2\right)}{2}=1$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.